Algospeak : how social media is transforming the future of language - Aleksic, Adam (Alfred A. Knopf, 2025)
"Algospeak is an energetic, astonishing journey into language, the internet, and what this intersection means for all of us. In it, a professional linguist uses original surveys, data, and internet archival research to usher us through this new linguistic landscape, he also illuminates how communication is changing in both familiar and unprecedented ways. From our use of emojis to sentence structure to the ways younger generations talk about sex and death (see unalive in English and desvivirse in Spanish), we are in a brand-new world, one shaped by algorithms and technology"-- Provided by publisher.